Crisis as potentiality: proximity care and the epidemic by Covid-19 - Terenzi Seixas, Clarissa (2020)
This article aims at questioning the privatizing hospital-centered biomedical model from the point of view of the response to the Covid-19 epidemic, which focuses on hospital care and hard and light-hard technologies. In this context, we argue that the governmental political project of defunding the public health system and other social policies severely aggravates this scenario. Putting under the spotlight the experiences of other countries, we present ‘Proximity Care’ as a territorial-based construction centered on light technologies for the production of highly complex care. Proximity Care appears under various shapes in the Brazilian National Health System (SUS) and has been presently underused. We show its potential for the creation of living networks of existence and the possibilities that it opens to reconfigure not only the model of coping with the epidemic, but also that of the post-pandemic.